HUBUNGAN KEEFEKTIFAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN MOTIVASI SEMBUH PENDERITA DIABETES MELLITUS DI RUANG KARANG ASAM RSUD I.A. MOEIS SAMARINDA - Kadir, Abd; Hafsyah, Delia Noor (Ensiklopedia of Journal, 2025)
Abstract: In 2021, there were 3,081 cases of Diabetes Mellitus, according to Samarinda City's Central Statistics Agency (2024). Nurses' therapeutic communication, which inspires and motivates patients to recover, is one external factor promoting recovery. 59 respondents were purposefully chosen for this cross-sectional descriptive analytical study. Motivation to recover was the dependent variable, and therapeutic communication was the independent variable. In the Karang Asam Room of I. A. Moeis Regional Hospital, Samarinda, nurses' therapeutic communication and patients' motivation to recover were found to be significantly correlated, according to a p-value of 0.001 <0.05 from univariate and bivariate data analysis using the Chi-Square test. In order to establish productive therapeutic relationships with patients, nurses are advised to improve their communication skillsKeywords: Diabetes Mellitus, Hospital, Motivation to recover, Therapeutic communication.